Anaisis Rasio Kecukupan Modal Kerja Pada PT Perkebunan Mitra Ogan Palembang - Bakti, Rendra (Universitas Muhammadiyah Palembang, 2019)
Purpose - Working capital is very important for any company, because almost all companies need working capital to finance day-to- day activities operasinal. Companies are required to constantly improve its efficiency so as to achieve the objectives expected by the company to achieve the optimal profit.Design/methodology - In the absence of sufficient working capital,the operational activities of a company may not run smoothly. This study aims to find out how the capital adequacy ratio. This research was conducted at PT Mitra Ogan plantation Palembang. The data used are secondary data from the financial statements Plantation Mitra Ogan Palembang.Findings - Where the results of analysis of the capital adequacy ratio at the company's work will provide an overview of how the company can manage its working capital well. If the company can use working capital well, it will obtain sufficient capital. Conversely, when the company suffered a shortage or reduction in working capital, will encourage companies to experience credit with a bank or other outside parties and may hamper the business operational.